2018
DOI: 10.1021/acs.orglett.8b01371
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Carboalumination of Alkynes Using Aluminum Trihalide and Silyl Ketene Imines: Stereo- and Regioselective Synthesis of Alkenylaluminum Compounds Bearing a Cyano Group

Abstract: An organoaluminum-free and catalyst-free anti-carboalumination of alkynes using aluminum trihalides and silyl ketene imines was developed. Three components, an alkyne, AlX, and a silyl ketene imine, were simply mixed to give the alkenylaluminum bearing a cyano group with regioselectivity. Theoretical calculations revealed the effective activation of the alkyne by AlX to enhance the regioselective carboalumination. The synthesized alkenylaluminums were applicable to many organic transformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Recently, we reported regioselective anti -carbometalations of alkynes using organosilicon nucleophiles and metal halides such as InBr 3 [ 40 ], GaBr 3 [ 41 ], BiBr 3 [ 42 ], ZnBr 2 [ 43 ], and AlBr 3 [ 44 ]. In our established carbometalations, a metal halide directly activates an alkyne, and then an organosilicon nucleophile adds to the alkyne from an opposite site of the metal halide.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported regioselective anti -carbometalations of alkynes using organosilicon nucleophiles and metal halides such as InBr 3 [ 40 ], GaBr 3 [ 41 ], BiBr 3 [ 42 ], ZnBr 2 [ 43 ], and AlBr 3 [ 44 ]. In our established carbometalations, a metal halide directly activates an alkyne, and then an organosilicon nucleophile adds to the alkyne from an opposite site of the metal halide.…”
Section: Resultsmentioning
confidence: 99%
“…Alkenylaluminum 245 with an allyl cyano group readily reacted with electrophilic azodicarboxylic esters, leading to useful N ‐alkenylhydrazides 246 (Scheme 65). [103] Theoretical calculations indicated that the transformation starts with activation of alkynes at the terminal carbon by aluminum, followed by the anti ‐attack of nucleophilic silyl ketene imines 244 to generate 245 regio‐ and stereoselectively. Intermediate 245 smoothly adds to azodicarboxylate ester to furnish ( E )‐ N ‐alkenylhydrazide 246 .…”
Section: Synthesis Of N‐alkenylhydrazidesmentioning
confidence: 99%